Dampak Poligami Tanpa Izin Istri Terhadap Kehidupan Rumah Tangga Ditinjau Menurut Hukum Keluarga Islam Di Indonesia - Riyan; Fadlan Muhajir; M Dwika Ardhana; M Afdul Soleh; Wizalkarnaen Hasibuan (Tabayyun : Journal Of Islamic Studies, 2024)
The phenomenon of polygamy without the consent of the previous wife is discussed in this paper, along with its implications for Islamic law. In order to get firsthand information regarding the phenomena of polygamy, this qualitative study interviewed informants with polygamous backgrounds, polygamous individuals, religious leaders, and community leaders. To thoroughly explain and implement a normative sociological approach, the analysis was conducted using a descriptive, qualitative methodology. The findings show that the community is ignorant about the legitimacy of polygamy and a number of important factors that should be taken into account, including how it would affect the family and the children, which could have an effect on the community as a whole. The law of polygamy in Islam states that it is acceptable for the husband to have a strong opinion against it. Nonetheless, given that the KHI's legal provisions prohibited polygamy without the consent of the former wife, this implies that, despite the husband's religious legitimacy, it is illegal under Indonesian administrative law.